2011
DOI: 10.1590/s1516-31802011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure due to primary amyloidosis: a case report and literature review

Abstract: CONTEXT: Primary amyloidosis, also known as AL amyloidosis, is commonly caused by clonal expansion of plasma cells in the bone marrow, thereby segregating light chains of clonal immunoglobulin that settle in tissues in the form of insoluble amyloid fibrils. The aim of this study was to report a case of primary amyloidosis with renal failure, diagnosed in Hospital São João, Porto, Portugal, focusing on the diagnostic difficulties and presenting a literature review. CASE REPORT:A 68-year-old Caucasian man was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Even feeding food products containing amyloid entities has been known to trigger systemic amyloidosis in the subjects . Consumption of aspartame has also been known to predispose nephrotoxic effects, and many studies have also revealed the occurrence of kidney dysfunction due to amyloidosis. These reports signify the possible relevance of both the amyloidogenic nature and the cross-seeding efficacy of the aspartame molecule to the mechanistic understanding of diverse metabolic disorders related to aspartame consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Even feeding food products containing amyloid entities has been known to trigger systemic amyloidosis in the subjects . Consumption of aspartame has also been known to predispose nephrotoxic effects, and many studies have also revealed the occurrence of kidney dysfunction due to amyloidosis. These reports signify the possible relevance of both the amyloidogenic nature and the cross-seeding efficacy of the aspartame molecule to the mechanistic understanding of diverse metabolic disorders related to aspartame consumption.…”
Section: Discussionmentioning
confidence: 99%